THE IMPORTANCE OF GOODS PRODUCTION AND INTERMEDIATE CONSUMPTION FOR AN INCREASED GDP - RADU-MARCEL JOIA (Challenges of the Knowledge Society)
Human existence is conditioned, of course, by the consumption of goods to meet the needs. Using the property to obtain other goods in this way is not consumption, but production. Goods that are the object of consumption can be natural or economic (created or produced by man). The natural goods that we can find in the human consumption, even if there are extremely important, there are not the subject of our attention because they are a gift of nature. In economics, the effect that a good is predicted to have during or after it is consumed is designated by the term of utility. In the context of a severe economic crisis, which determines a real sacrifice of consumer’s wishes, under the impact of budgetary constraint, the utility and the consumer optimum suffer various modifications.Increasingly limited resources and low incomes lead to more people sacrifices concerning the goods that they will consume, respectively purchase. So we consume less, we produce less, causing a reduction in GDP. The economical crisis, through its effects has changed the people consumption habitudes by editing it according to the available resources. Manufacturers, in the absence of profits will be forced to find new solutions to attract consumers.The main objective of this paper is to highlight the relationship that exists between the consumption, goods and services production and GDP. In terms of economics, the goods and services production and intermediate consumption directly influence GDP, as two independent variables and dependent GDP. We performed a simple regression model based on a series of data in Romania, during 1995-2009, to evidence the importance of the two independent variables in obtaining an increased GDP.